Racism in Ralph Ellison's Invisible Man - Muthanna, Ansam (International Journal of Psychosocial Rehabilitation, 2020)
Ralph Ellison's Invisible Man (1947) is the story of an anonymous, young Black protagonist's geographical and psychological journey to fulfill a desire to become a Black leader and his ultimate failure to do so. Invisible Man is a novel about an anonymous young black male identity. The unnamed African American narrator embarks on a quest for political empowerment and self-fulfillment in the segregated United States in the 20th century. Believing that he can't transcend the normative aspects of the racist screen by which white Americans uniformly apprehend him, the protagonist succumbs to the idea of being an invisible man. Because of his oratory talent, the protagonist gains the opportunity to become a Black leader; in the end, however, he discovers his own invisibility in American society. Secluding himself in the underground, the protagonist narrates how he became aware of his invisibility.